Enhancing Customer Loyalty: Optimizing Barista and Store Atmosphere for Increased Customer Satisfaction - Alfiansyah, Rifky; Pamungkas, Rafly Abdi; Bakhri, Saeful; Romdonny, Jefry (International Journal of Social Service and Research, 2024)
The aim of this study was to investigate the impact of store atmosphere and baristas on customer loyalty, mediated by customer satisfaction as an intervening variable. The study was conducted with the hope of enhancing customer loyalty in coffee shops located in the city of Cirebon. Convenience sampling was employed in this study. The primary data was collected by distributing questionnaires to 115 consumers in coffee shops located in Cirebon city. The data was analysed using partial least squares (SEM-PLS) structural equation modelling with the Smart-PLS 3.0 application. The study's results indicate that the store's atmosphere has a positive impact on customer satisfaction and loyalty. Additionally, the barista variable was found to have a positive effect on customer satisfaction and loyalty. It was found that the customer satisfaction variable mediated the relationship between store atmosphere and baristas on customer loyalty. Achieving customer loyalty is not solely dependent on the store atmosphere and baristas. It is important to explore other variables that can contribute to this goal. Future researchers should investigate these variables further.